2022
DOI: 10.3390/life12030462
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Photo-Cycles in the Modulation of Growth and Biochemical Profile of Microalgae: Part I—Food Interest Compounds

Abstract: The objective of this work was to evaluate the effect of different photo-cycles on the growth and biochemical profile of Scenedesmus obliquus CPCC05, focusing on food interest compounds. The photo-cycle conditions were separated into three groups: long-term photo-cycles (24:0, 22:2, 20:4, 18:6, 12:12, and 10:14 (h:h)), frequency photo-cycles (2, 4, 8, 12, 24, and 48 times per day (t/d)), and short photo-cycles (0.91:0.09, 0.83:0.17, 0.75:0.25, and 0.50:0.50 (s:s)) of light:dark, respectively. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…In experiments on the effect of light exposure on the productivity of microalgae, various photoperiods (e.g., 12:12, 14:10, 16:8, 24:0-h light/dark cycles) were tested [ 17 , 18 , 19 ]. It has been shown that a longer period of darkness can reduce the productivity of algae as it inhibits the functioning of the cell photosystems [ 20 ]. The optimal light/dark cycle determines the algal culture growth rate, total biomass yield, accumulation of proteins, lipids, and carbohydrates, as well as the uptake of macro- and microelements [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In experiments on the effect of light exposure on the productivity of microalgae, various photoperiods (e.g., 12:12, 14:10, 16:8, 24:0-h light/dark cycles) were tested [ 17 , 18 , 19 ]. It has been shown that a longer period of darkness can reduce the productivity of algae as it inhibits the functioning of the cell photosystems [ 20 ]. The optimal light/dark cycle determines the algal culture growth rate, total biomass yield, accumulation of proteins, lipids, and carbohydrates, as well as the uptake of macro- and microelements [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Con-sidering that the high tested light intensities can cause photoinhibition of microalgae [35], in this work, cultivation was carried out both under continuous and periodic light. It is also known that the use of different photoperiods makes it possible to change the biochemical composition of microalgal cells [9,36]. A series of experiments were carried out to analyze the effects of daily PPFD (37.44-112.32 mol m −2 day −1 ), photoperiods (16 h and 24 h), and various CO 2 concentrations (1-4%) on algal growth, biomass productivity, nutrient removal, and accumulation of selected metabolic products in a well-controlled Labfors 4 Lux photobioreactor.…”
Section: Introductionmentioning
confidence: 99%